Proposed upgrading of budget hotel for Heritage Hotel at Bangunan Stesen Keretapi, Jalan Sultan Hishamuddin, 50050,Kuala Lumpur / Mas 'Aqilah Zaini - Zaini, Mas 'Aqilah (Faculty of Architecture, Planning and Surveying, 2010)
This report writing is about the upgarding proposal of budget hotel for The Heritage Hotel.This final project duration is about 4 months. The scope of work for this project is including making some observation and analysis about client, the site and to propose a design solution according to the problem and requirement from client.This project’s site project is located at Kuala Lumpur Old Railway Station Building, Jalan Sultan Hishamuddin, Kuala Lumpur.The Heritage Hotel is targeting to increase 50 percent of their customer in year 2010. For now, the Heritage Hotel have their own image, however, the owner want to change their hotel is look to be updated with trend, yet they still maintaining the neo-classical character in its interior. For the upgrading work, they want to focus on few areas, which is the reception, waiting area, cafe and rooms. They are a few ways that have been used to observe the design problem that need to be solved and getting the information data, such as having some discussion with the hotel manager, making some observation about the design problem at site and take some visitor’s opinion on the internet.